2021
DOI: 10.1021/acsami.1c18250
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hydrogel Capable of In Situ Covalent Crosslinking for Permanent Embolization

Abstract: Vascular embolization provides an effective approach for the treatment of hemorrhage, aneurysms, and other vascular abnormalities. However, current embolic materials, such as metallic coils and liquid embolic agents, are limited by their inability to provide safe, consistent, and controlled embolization. Here, we report an injectable hydrogel that can remain at the injection site and subsequently undergo in situ covalent crosslinking, leading to the formation of a dual-crosslinking network (DCN) hydrogel for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The chemical crosslinking results in fast and stable hydrogel formation with a high mechanical strength based on Michael addition reactions, [25,164,165] Schiff base reactions, [166,167] or photocrosslinking. [35,168] The covalent crosslinking between the polymer chains results in the solidification of hydrogels in situ to occlude the blood vessels.…”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The chemical crosslinking results in fast and stable hydrogel formation with a high mechanical strength based on Michael addition reactions, [25,164,165] Schiff base reactions, [166,167] or photocrosslinking. [35,168] The covalent crosslinking between the polymer chains results in the solidification of hydrogels in situ to occlude the blood vessels.…”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
“…In vivo embolization on rabbits further demonstrated that the DCN hydrogels could achieve immediate embolization of the femoral artery with long-term occlusion, which could be ascribed to the efficient hemostatic capability, desirable mechanical properties, and stability of the DCN hydrogels. [25] In another study, Lim et al developed a double-crosslinked alginate-based hydrogel (DAT) for treating aneurysms. The photocrosslinkable alginate was mixed with Ta nanopowder and the mixture was continuously spun into hydrogel microfibers via in situ photocrosslinking, followed by ionic crosslinking using Ca 2+ in the blood (Figure 12B).…”
Section: Dual-crosslinking Hydrogelsmentioning
confidence: 99%
See 3 more Smart Citations